The Intersection of LGBTQ+ Mental Health and the Rise of Same-Sex Marriage: Understanding Current Trends and Implications for LGBTQ+ Rights and Society - Khumukcham Anupama Devi; Thokchom Soniya Devi; Sudhakar Kumar Singh (International Journal of Medical Research and Review, 2024)
The LGBTQ+ community has long faced discrimination, prejudice, and marginalization, which have had significant impacts on their mental health and well-being. Studies have shown that LGBTQ+ individuals are at a higher risk of experiencing mental health disparities compared to their heterosexual and cisgender counterparts (Indian Journal of Psychiatry, 2017; India HIV/AIDS Alliance, 2019). However, in recent years, there have been significant advancements in LGBTQ+ rights and recognition, including the increasing acceptance and legal recognition of same-sex marriage in many countries around the world, including India. These developments have important implications for the mental health and well-being of LGBTQ+ individuals, as marriage is a significant institution that can impact various aspects of an individual’s life, including their mental health and relationships.